Delayed onset of striatal projection neuron hyperexcitability in Fmr1−/y mice - Nelson, Lars; Janeček, Michael; Matarazzo, Michael; Shih, Yi-Chun; Peixoto, Rui T. (Frontiers in Cellular Neuroscience, 2025)
IntroductionFragile X Syndrome (FXS), the most common genetic cause of intellectual disability and autism spectrum disorder (ASD), results from silencing of the FMR1 gene and consequent loss of Fragile X Messenger Ribonucleoprotein (FMRP). FMRP deficiency disrupts neural development, leading to behavioral and motor deficits associated with striatal dysfunction. Although structural and functional abnormalities in striatal projection neurons (SPNs) have been observed in adult Fmr1 knockout mice (Fmr1−/y), their developmental onset and contribution to early FXS pathophysiology remain unknown.MethodsWe examined the postnatal maturation of SPNs in the dorsomedial striatum (DMS) of Fmr1−/y mice, assessing glutamatergic synaptic inputs and intrinsic excitability using whole-cell electrophysiology.ResultsDuring postnatal development, Fmr1 deficient SPNs display normal synaptic and intrinsic properties, consistent with typical maturation. In contrast, by P60, Fmr1−/y SPNs exhibit pronounced hyperexcitability in both dopamine D1 receptor–expressing SPNs (D1-SPNs) and D2 receptor–expressing SPNs (D2-SPNs), with more pronounced effects in D1-SPNs. Chronic aripiprazole treatment, a widely prescribed therapy for behavioral symptoms in FXS, fails to normalize SPN excitability, suggesting limited efficacy in addressing core SPN dysfunction.DiscussionThese findings reveal that DMS SPN hyperexcitability in Fmr1−/y mice emerges after early postnatal development, pointing to a progressive trajectory of striatal abnormalities. In addition, these results underscore the importance of developmental timing in FXS pathophysiology and emphasize the need for targeted interventions to address SPN dysfunction.